Reversal of Small, Dense LDL Subclass Phenotype by Normalization of Adiposity - Siri-Tarino, Patty (2009)
Excess adiposity and high-carbohydrate diets have been associated with an atherogenic lipoprotein phenotype (ALP) characterized by increased concentrations of small, dense low-density lipoprotein (LDL) particles (pattern B). We tested whether weight loss and normalization of adiposity could reverse ALP in overweight men with pattern B. After consuming a moderate-carbohydrate, high-fat diet for 3 weeks, pattern B and nonpattern B (pattern A) men were randomized to a weight loss (n = 60 and n = 36, respectively) or control weight-stable arm (n = 20 and n = 17, respectively). Men in the weight loss arm consumed ∼1,000 fewer calories per day over 9 weeks to induce an average ∼9 kg weight loss. In the control group, weight stability was maintained for 4 weeks after randomization. Weight loss led to the conversion of pattern B to pattern A in 58% of baseline pattern B men. Among men who achieved BMIs of <25kg/m(2) (62% of pattern B men vs. 83% of pattern A men), 81% of pattern B men converted to pattern A. Weight loss was associated with a significantly greater decrease in small, dense LDL subclass 3b in pattern B relative to pattern A men. The lipoprotein profiles of pattern A men who converted from pattern B were comparable to those of men with pattern A at baseline. Conversion of LDL subclass pattern B to pattern A and reversal of ALP can be achieved in a high proportion of overweight men by normalization of adiposity.